CFD simulation and experimental validation of ethanol adsorption onto activated carbon packed heat exchanger. (February 2017) - Jribi, Skander; Miyazaki, Takahiko; Saha, Bidyut Baran; Koyama, Shigeru; Maeda, Shinnosuke; Maruyama, Tomohiro
Highlights: Temperature response of finned tube adsorber was simulated using Fluent software. Good agreement between experimental and simulated temperatures was obtained. Heat released by gas friction was higher than the heat of adsorption. Refrigerant gas shows difficulty in reaching adsorbent with higher thicknesses. Abstract: Experimental validation of simulated adsorber/desorber beds for sorption cooling applications is essential to obtain reliable results. We have conducted rigorous simulation of the adsorption process occurring in a finned tube adsorber utilizing 2D-axisymmetric geometry. The adsorber uses activated carbon–ethanol as adsorbent–refrigerant pair. It is cooled with water at nearly 30 °C and experiencing a sharp pressure increase of ethanol from 0.95 kPa initially to 6 kPa. The simulated temperatures at adsorbent thicknesses of 0, 1, 5 and 10 mm from tube outer diameter showed an increase in adsorbent temperature up to 20 °C from its initial temperature. They were slightly higher at start of adsorption and were consistent with experimental data at higher flow time. The validated CFD model will serve as a base for evaluating and optimizing activated carbon–ethanol adsorption cooling cycle. It can be extended also to different adsorber designs and other adsorbent–adsorbate pairs.